The neurophysiological correlates of the visual after-images - Laugalys , Feliksas (Psichologija, 1981)
A short review of neurophysiological correlates of human visual after-images is presented in the article. Some temporal parameters of bright and dark phases of human visual after-images are compared with the corresponding parameters of a single unit activity of contralateral neurons. By way of illustration, our own investigations of the single unit activity of the lateral geniculate body of rabbits evoked by a brief (10 ms duration) retinal light illumination have been used. The necessity to investigate not only monocular (contralateral), but also binocular (ipsilateral and contralateral) recovery cycles of single units of various visual nervous system structures is emphasized. An attempt is made to consider the hypotheses which suggest an explanation of nature of inhibition in the visual system. The experimental evidences provided by other authors and achieved on the basis of the extracellular and intracellular investigations have been used in the present article, with the view of explaining the inhibition by means of postsynaptic hyperpolarization if the stimuli presented to the retina are brief and diffuse. Some considerations on the biological role of inhibition have been discussed.
Keywords: neurophysiology; after-images; the neurophysiological correlates of the visual after-images